Analisis Kesalahan Penggunaan Modalitas Epistemik dan Deontik Hazu Dan Beki pada Pembelajar Tingkat Menengah - Ghandur Muhammad Daffa; Dedi Sutedi; Herniwati Herniwati (Universitas Pendidikan Indonesia, 2022)
This study aims to obtain an overview of the errors in the use of hazu and beki modalities that occur in intermediate Japanese learners. This research is motivated by the similarity of the meanings of these two modalities if they are changed into Indonesian. This is what makes it difficult for students to use these two modalities. The method used in this study is a qualitative descriptive method supported by quantitative data. The instruments used were tests and questionnaires. Then, through the results of data analysis, it is known that the beki modality is the modality that has more errors than the hazu modality. It is also known that the meaning of the beki modality which expresses regret is the meaning of the beki modality which is the most prone to errors. As for the hazu modality, the meaning of the hazu modality which states a logical conclusion is the meaning of the hazu modality which is the most prone to errors. Furthermore, the type of alternating form error is the most common type of error that occurs in this study. This makes there is a tendency that the mistakes that occur in this middle-level learner are errors due to the respondent's competency factor.